Pengaruh Nilai Neraca Perdagangan Internasional Indonesia Terhadap Kurs Rupiah (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
Lionintan Andini Putri, 2019. Effect of International Trade Balance Value Indonesian Rupiah against under the guidance of Mrs. Theresia Militina and Mr. Michael. This study aimed to determine the effect of the value of Indonesia's international trade balance current year and the previous year's trade balance value of the rupiah exchange rate. The research was done using analysis tools Distributed Lag Models (Time Series). The data used in this research is secondary data within a period of fifteen years from the period 2003 to 2017. The available data were processed using SPSS (Stastistical Package for Social Science) version 21. The results showed that the value of Indonesia's international trade balance current year (2017) and no significant negative impact on the rupiah exchange rate. Indonesia's international trade balance value of the previous year (2016) and no significant negative impact on the rupiah exchange rate. Indonesia's international trade balance value two years earlier (2015) and no significant negative impact on the rupiah exchange rate. The value of the international trade balance Indonesia three years earlier (in 2014) a significant negative effect on the exchange rate of the rupiah.